2017
DOI: 10.1007/s10508-017-0946-0
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Attachment in Transsexual Adults

Abstract: The main aim of this study was to investigate the associations between personality features and attachment patterns in transsexual adults. We explored mental representations of attachment, assessed personality traits, and possible personality disorders. Forty-four individuals diagnosed with gender identity disorder (now gender dysphoria), 28 male-to-female and 16 female-to-male, were evaluated using the Shedler-Westen assessment procedure-200 (SWAP-200) to assess personality traits and disorders; the adult att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 63 publications
3
9
0
1
Order By: Relevance
“…It is interesting to note that the literature data highlights high percentages of disorganization in clinical samples ( Allen et al, 1996 ; West et al, 2001 ; Steele et al, 2003 ; Agrawal et al, 2004 ; Stovall-McClough and Cloitre, 2006 ; Harari et al, 2007 ; Ivarsson, 2008 ; Farina et al, 2014 ; Murphy et al, 2014 ) and high psychosocial risk ( Stalker and Davies, 1995 ; Lyons-Ruth et al, 2003 ; Crowell and Hauser, 2008 ). Specifically, with respect to GD samples, the high occurrence of U and CC in our group confirmed the association between disorganized patterns and transsexualism that has been found in previous studies ( Cook, 1999 ; Vitelli and Riccardi, 2010 ; Lingiardi et al, 2017 ). Moreover, the heterogeneity of disorganized profiles that defined our GD sample denoted the presence of both a local breakdown in discourse strategies regarding loss or abuse and a global disruption of attachment strategies along the entire transcript.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is interesting to note that the literature data highlights high percentages of disorganization in clinical samples ( Allen et al, 1996 ; West et al, 2001 ; Steele et al, 2003 ; Agrawal et al, 2004 ; Stovall-McClough and Cloitre, 2006 ; Harari et al, 2007 ; Ivarsson, 2008 ; Farina et al, 2014 ; Murphy et al, 2014 ) and high psychosocial risk ( Stalker and Davies, 1995 ; Lyons-Ruth et al, 2003 ; Crowell and Hauser, 2008 ). Specifically, with respect to GD samples, the high occurrence of U and CC in our group confirmed the association between disorganized patterns and transsexualism that has been found in previous studies ( Cook, 1999 ; Vitelli and Riccardi, 2010 ; Lingiardi et al, 2017 ). Moreover, the heterogeneity of disorganized profiles that defined our GD sample denoted the presence of both a local breakdown in discourse strategies regarding loss or abuse and a global disruption of attachment strategies along the entire transcript.…”
Section: Discussionsupporting
confidence: 91%
“… Colizzi et al (2013) found a high percentage of insecure attachment (70%) in their sample of 50 adult transsexuals. Finally, in a recent study, Lingiardi et al (2017) found a high percentage of unresolved/disorganized states of mind (50%) and a considerably high percentage of secure patterns (39%). Moreover, 29 (66%) of the 44 individuals had traumatic childhood experiences relating to the loss of an attachment figure or physical or sexual abuse.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This may mean that gender diversity in developmental age receives less attention than it deserves. However, despite the apparently low numbers of referrals and centers compared with other countries, the improved diagnostic accuracy and the intensified resonance and media visibility of transgender lives have led to an increase in Italian studies on this topic (Amodeo et al, 2018; Fisher et al, 2013; Giovanardi et al, 2018, 2019; Lingiardi et al, 2017; Ristori et al, 2020; Scandurra et al, 2018; Vitelli et al, 2017; Vitelli & Riccardi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mental health conditions have been reported to have higher prevalence within transgender populations and there have been many reports of high rates of depression and anxiety 6–8 occurring in transgender adults. There also has been a suggestion that personality disorders 9,10 and eating disorders 11 may be more prevalent among transgender individuals. Co-occurrence with ASD has been described in children and adolescents, 12,13 and while much of the literature has associated autism traits detected on screening tests with gender dysphoria, 14,15 only one study has assessed prevalence of the diagnosis of ASD among adult transgender individuals.…”
Section: Introductionmentioning
confidence: 99%